2013
DOI: 10.1080/14786419.2013.771348
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and antimicrobial activity of propolis-associated fungi

Abstract: Propolis is a natural product widely known for its medicinal properties. In this work, fungi present on propolis samples were isolated, identified and tested for the production of antimicrobial metabolites. Twenty-two fungal isolates were obtained, some of which were identified as Alternaria alternata, Aspergillus flavus, Bipolaris hawaiiensis, Fusarium merismoides, Lasiodiplodia theobromae, Penicillium citrinum, Penicillium crustosum, Penicillium janthinellum, Penicillium purpurogenum, Pestalotiopsis palustri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
1
4
0
7
Order By: Relevance
“…examinadas, pero con variaciones en la CMI y CMF, al respecto la mayor actividad biológica la mostraron los extractos etanólicos de propóleos de Alemania e Italia versus los de España y Venezuela atribuible este hallazgo a la variabilidad en la composición química ya registrada en varias regiones del mundo, ya que, hasta ahora, aunque se tienen indicios, no se ha demostrado que exista una sustancia individual o un grupo de ellas que sea la responsable directa de la actividad biológica y se cree que las diferencias en cuanto a CMI y CMF se deba a una acción sinérgica entre diferente compuestos característicos de cada propóleos [23]- [24]- [25]- [26]. C.albicans ----…”
Section: Discussionunclassified
“…examinadas, pero con variaciones en la CMI y CMF, al respecto la mayor actividad biológica la mostraron los extractos etanólicos de propóleos de Alemania e Italia versus los de España y Venezuela atribuible este hallazgo a la variabilidad en la composición química ya registrada en varias regiones del mundo, ya que, hasta ahora, aunque se tienen indicios, no se ha demostrado que exista una sustancia individual o un grupo de ellas que sea la responsable directa de la actividad biológica y se cree que las diferencias en cuanto a CMI y CMF se deba a una acción sinérgica entre diferente compuestos característicos de cada propóleos [23]- [24]- [25]- [26]. C.albicans ----…”
Section: Discussionunclassified
“…Discovering new species and interesting bioactive compounds from customary sources is becoming progressively laborious. Among the few studies being conducted to study propolis microbial communities, only the work of De Souza et al [ 30 ] provided insights into fungi living in propolis. Here, we describe the first detailed investigation of the cultivable fungal community associated with Tunisian propolis samples based on a cultivation approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it could conceivably be used as an antiinflammatory [ 24 , 25 ], antioxidant [ 26 ], and anticancer agent [ 27 ], in addition to a reported antiprotozoal effect [ 28 , 29 ]. In recent years, the roles of propolis-associated microbes are increasingly studied [ 30 32 ]. Also, it has been revealed that propolis has the highest microbial community richness among hive components [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Candida é um genêro que pode ser facilmente encontrada no corpo do homem e de animais, colonizando a pele e mucosas dos tratos digestivo e urinário, bucal e genital, sendo a C. albicans, a mais ralatada, seguida de C. parapsilosis, C. glabrata, C. tropicalis e C. krusei (HORN et al, 2009;PANIZO et al, 2009). Ressaltando que a própolis é uma fonte promissora de fungos, que produzem agentes ativos contra bactérias particularmente, responsáveis por intoxicações alimentares relevantes (SOUZA et al, 2013).…”
Section: Tipo Espécieunclassified